Community Based Tourism Village Planning in Kuningan Regency, West Java - Nining Wahyuningsih; Diana Djuwita (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2021)
The purpose of this study was to determine the potential of Padabeunghar Village to establish a Community Based Tourism Village, formulate a community-based tourism village planning model in Padabeunghar Village, and assess the Kuningan District Government's efforts in forming a village-based tourism community in Padabeunghar Village. The research method used is a qualitative approach. Data collection was carried out through in-depth interviews with informants, including DinasPemuda, Olahraga, and Pariwisata, DinasLingkunganHidup, the Padabeunghar Village Government, Kompepar, manager of Kebun Raya Kuningan, TNGC, and community representatives. The results showed that Padabeunghar Village has potential that supports village tourism planning, such as natural potential, institutional potential (local community), and the potential of local wisdom products. The Padabeunghar Tourism Village planning model involves various stakeholders, both internal and external, where each party has different roles and responsibilities and can coordinate with each other to create a sustainable tourism village. The efforts of the Kuningan regency government in community-based tourism planning are as facilitators who provide assistance, training, and empowerment to the Padabeunghar community and change their mindset so they want to develop themselves.Keywords: Community Based Tourism, facilitators, tourism planning